Asymmetric Intramolecular Hydroamination of Alkenes in Mild and Wet Conditions—Structure and Reactivity of Cationic Binuclear Gold(I) Catalysts. Issue 8 (9th July 2014) - Abadie, Marc‐Antoine; Trivelli, Xavier; Medina, Florian; Capet, Frédéric; Roussel, Pascal; Agbossou‐Niedercorn, Francine; Michon, Christophe
Abstract A selected diphosphine binuclear gold(I) chloride complex was combined with a silver salt to catalyze efficiently, for the first time, the asymmetric intramolecular hydroamination of alkenes with high conversions and enantioselectivities, in mild conditions and in presence of water. Both enantiomers of the products could be obtained by controlling the molecular ion‐pairs through the solvent polarity. The gold(I) cationic active species was characterized unambiguously at the solid state by X‐ray analysis and in solution by DOSY 1H NMR experiments. No contribution of silver chloride was observed on the bonding mode of the catalyst.